Characterization of the bee community and pollination network in a southeastern U.S. pine savanna - Ulyshen, Michael D.; Robertson, Kevin; Horn, Scott; Dixon, Cinnamon (Frontiers in Ecology and Evolution, 2024)
Although the fire-maintained pine savannas of the southeastern U.S. Coastal Plain are recognized for their plant diversity, pollinators associated with these ecosystems remain comparatively understudied. Here we present the results from a season-long effort to record bee-flower interactions at a single site in Florida.We collected 93 bee species (out of an estimated 117) from 79 flower species, with a total of 446 unique interactions. Bee richness and the number of interactions exhibited a bimodal pattern, dipping in midsummer before an estimated peak in October. The most important floral resources changed throughout the season as did the composition of bees, with the spring and fall periods being particularly distinct. We found that pollen specialists (that collect pollen from a single family of plants) and pollen generalists accounted for a similar proportion of bee species over the entire season. However, pollen generalists outnumbered pollen specialists in the spring and summer before reversing in the fall. Pollen specialists visited significantly fewer plant species and families than pollen generalists and many were collected exclusively from their host family. This was particularly the case for aster specialists active only during the fall. We estimate that between 18.3-25.8% of the local bee fauna depends directly on the overstory trees for nesting habitat including dead wood and resin. Two management recommendations can be made based on these results. First, because fall is the period of peak floral abundance and bee richness, including many late-season aster specialists, it is probably the least favorable time for prescribed fire.Second, considering that a significant proportion of native bees depend on dead wood for nesting, it is important to retain standing dead trees and fallen wood whenever possible.